The implementation of Shariah compliant hotel: a case study of Pulai Springs Resort Berhad / Zuliana Zoolkefli … [et al.] - Zoolkefli, Zuliana (2015)
This study specifically discusses issues on the implementation of Shariah compliant hotel at Pulai Springs Resort. The findings will give Pulai Springs Resort broader scope on appropriate actions on implementing Shariah compliant based hotel thus identifying current Shariah practices currently applied by Pulai Springs Resort.